Electrical design and testing of a 500 kW doubly fed induction generator for wind power applications - (:unkn) unknown (My University, 2017)
0

In this study, the electrical design and testing of a 500 kW doubly fed induction generator (DFIG) is presented, developed in the context of the MILRES (Turkish National Wind Energy Systems) Project. The main objective of the MILRES Project is to encourage locally produced equipment for wind power systems. Therefore, in the DFIG design, the standard construction capabilities of the local machine manufacturers are especially taken into consideration. In this way, it is aimed that the designed DFIG can easily and cost-effectively be manufactured by local machine manufacturers in Turkey. In the DFIG design procedure, initially, an analytical design of the DFIG is performed depending on speci ed design criteria. Then the analytical design is veri ed by using nite element analysis. Depending on the obtained results in electromagnetic analyses, the DFIG design is modi ed in order to improve the obtained performance further. Finally, the designed DFIG is manufactured and its performance tests are performed at three different operating points. The test results verify the analyses results and show that the designed DFIG satis es the desired performance criteria.
Keywords: Mühendislik, Elektrik ve Elektronik